2021
DOI: 10.21203/rs.3.rs-696563/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Healthy Female Microbiome Across Body Sites: Effect of Hormonal Contraceptives and the Menstrual Cycle

Abstract: Background: There is increasing evidence that the vaginal microbiome influences women’s health. V agina l dysbiosis with a low abundance of L actobacillus h as been connected to gynaecological and obstetric complications. However, the interplay between the vaginal microbiome and the microbiome in other body sites is not yet described. In addition, fluctuating endogenous sex hormones may exert an effect on microbiome composition and are markedly changed by hormonal contraception . This study includes a cohort o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Different microbiota characteristics are observed in women at different physiological stages [30] . In healthy women of reproductive age, the vaginal microbiome composition changes dramatically before and after menstruation [31] . Menstrual blood owing through the vagina leaves su cient iron for pathogens, and the iron necessary for pathogen metabolism [32] , which is reduced by the iron-binding a nity of lactoferrin, is replenished.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different microbiota characteristics are observed in women at different physiological stages [30] . In healthy women of reproductive age, the vaginal microbiome composition changes dramatically before and after menstruation [31] . Menstrual blood owing through the vagina leaves su cient iron for pathogens, and the iron necessary for pathogen metabolism [32] , which is reduced by the iron-binding a nity of lactoferrin, is replenished.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies measuring estradiol levels and vaginal microbiome composition in women who use oral contraceptives to inhibit ovulation have shown that the high diversity observed during menstruation is mainly driven by estradiol withdrawal before menstruation rather than by the dynamic drive of progesterone. Lactobacillus abundance increases during the follicular and luteal phases, gradually normalizing the vaginal microecology [31,33] . Under the in uence of this periodicity, combined with our test results, we found different types of dominant bacterial pro les in patients with adenomyosis in both the both luteal and follicular stages, which provided a reference for the detection of biomarkers in patients with speci c menstrual cycles or to evaluate their e cacy.…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus relative abundance during menses (51)(52)(53)(54)(55)(56). To determine if the HMb mice vaginal microbiota is influenced by estrous stage, five HMb mice were swabbed daily for one week.…”
Section: The Human Vaginal Microbiota Displays Modest Fluctuations In...mentioning
confidence: 99%